The clinical and radiological outcomes of hip resurfacing versus total hip arthroplasty: a meta-analysis and systematic review - Smith, Toby O (Informa Healthcare, 2010)
BACKGROUND AND PURPOSE: Hip resurfacing (HRS) procedures have gained increasing popularity for younger, higher-demand patients with degenerative hip pathologies. However, with concerns regarding revision rates and possible adverse metal hypersensitivity reactions with metal-on-metal articulations, some authors have questioned the hypothesized superiority of hip resurfacing over total hip arthroplasty (THA). In this meta-analysis, we compared the clinical and radiological outcomes and complication rates of these 2 procedures. METHODS: A systematic review was undertaken of all published (Medline, CINAHL, AMED, EMBASE) and unpublished or gray literature research databases up to January 2010. Clinical and radiological outcomes as well as complications of HRS were compared to those of THA using risk ratio, mean difference, and standardized mean difference statistics. Studies were critically appraised using the CASP appraisal tool. RESULTS: 46 studies were identified from 1,124 citations. These included 3,799 HRSs and 3,282 THAs. On meta-analysis, functional outcomes for subjects following HRS were better than or the same as for subjects with a THA, but there were statistically significantly greater incidences of heterotopic ossification, aseptic loosening, and revision surgery with HRS compared to THA. The evidence base showed a number of methodological inadequacies such as the limited use of power calculations and poor or absent blinding of both patients and assessors, possibly giving rise to assessor bias. INTERPRETATION: On the basis of the current evidence base, HRS may have better functional outcomes than THA, but the increased risks of heterotopic ossification, aseptic loosening, and revision surgery following HRS indicate that THA is superior in terms of implant survival.